Peningkatan Kapasitas UMKM Kampung Sukan Tengah melalui Pelatihan Storytelling Produk dan Pemasaran Digital Berbasis WhatsApp Business - Winda Jubaidah; Siti Munawaroh; Safitri Nurhidayati; Ammar Fanani; Bambang Budi Oetomo (Pusat Riset dan Inovasi Nasional, 2025)
This community service program was designed to strengthen the marketing capabilities of MSMEs in Kampung Sukan Tengah, Berau, by integrating product storytelling techniques and WhatsApp Business-based digital marketing strategies. The program employed a participatory approach, namely Asset-Based Community Development (ABCD) and Participatory Action Research (PAR), ensuring active participation from the planning stage through evaluation. The program consisted of a one-day intensive workshop with 25 MSMEs, followed by three weeks of online mentoring to ensure consistent application of the acquired skills. Data collection included pre- and post-tests, observation sheets during the training, and a follow-up survey after the program concluded. The results were significant: 80% of participants successfully compiled product catalogs, created automatic replies, and managed their business profiles on WhatsApp Business. Furthermore, 90% of respondents reported increased confidence in communicating their product value propositions, while 60% reported increased sales within three to four weeks of the mentoring session. The discussion connects these achievements to recent literature on MSME digitalization, narrative-based promotions, and mobile-first marketing trends. The results show that the use of simple, accessible, and locally relevant tools, when combined with engaging storytelling strategies, can accelerate digital adoption in rural areas. However, the program's sustainability remains dependent on digital infrastructure support, consistent mentoring, and the involvement of various parties. The program emphasizes the importance of synergy between universities, local governments, and MSME communities to replicate similar practices on a broader scale. Practical recommendations are also provided, including strengthening internet networks, developing applicable training modules, and building a collaborative ecosystem for MSMEs to compete in the digital marketplace.